Establishing a sustainable development goal for oceans and coasts to face the challenges of our future ocean - Martin Visbeck; Ulrike Kronfeld-Goharani; Barbara Neumann; Wilfried Rickels; Jörn Schmidt; Erik van Doorn (Kiel Institute for the World Economy (IfW), 2013)
Oceans regulate our climate, provide us with natural resources such as food, materials, substances, and energy and are essential for international trade, recreational, and cultural activities. Free access to and availability of ocean resources and services, together with human development, have put strong pressures on marine ecosystems, ranging from overfishing and reckless resource extraction to various channels of careless pollution. International cooperation and negotiations are required to protect the marine environment and use marine resources in a way that the needs of future generations will be met. For that purpose, developing and agreeing on a Sustainable Development Goal (SDG) Oceans and Coasts could be an essential element for sustainable ocean management. The SDGs will build upon the Millennium Development Goals (MDG) and replace them by 2015. Even though ensuring environmental sustainability is one of the eight MDG goals, the ocean is not explicitly included. Furthermore, the creation of a comprehensive underlying set of oceanic sustainability indicators would help assessing the current status of marine systems, diagnose on-going trends, and provide information for forward-locking and sustainable ocean governance.
Keywords: Q56; Q57; Q58; 330; sustainable development; ocean; sustainability indicators